Triceps Surae Muscle Architecture Adaptations to Eccentric Training - Geremia, Jeam Marcel; Baroni, Bruno Manfredini; Bini, Rodrigo Rico; Lanferdini, Fabio Juner; de Lima, Amanda Rodrigues; Herzog, Walter; Vaz, Marco Aurélio (Frontiers in Physiology, 2019)
Background Eccentric exercises have been used in physical training, injury prevention, and rehabilitation programs. The systematic use of eccentric training promotes specific morphological adaptations on skeletal muscles. However, synergistic muscles, such as the triceps surae components, might display different structural adaptations due to differences in architecture, function, and load sharing. Therefore, the purpose of this study was to determine the effects of an eccentric training program on the triceps surae (GM, gastrocnemius medialis; GL, gastrocnemius lateralis; and SO, soleus) muscle architecture. Methods Twenty healthy male subjects (26 ± 4 years) underwent a 4-week control period followed by a 12-week eccentric training program. Muscle architecture [fascicle length (FL), pennation angle (PA), and muscle thickness (MT)] of GM, GL, and SO was evaluated every 4 weeks by ultrasonography. Results Fascicle lengths (GM: 13.2%; GL: 8.8%; SO: 21%) and MT (GM: 14.9%; GL: 15.3%; SO: 19.1%) increased from pre- to post-training, whereas PAs remained similar. GM and SO FL and MT increased up to the 8th training week, whereas GL FL increased up to the 4th week. SO displayed the highest, and GL the smallest gains in FL post-training. Conclusion All three synergistic plantar flexor muscles increased FL and MT with eccentric training. MT increased similarly among the synergistic muscles, while the muscle with the shortest FL at baseline (SO) showed the greatest increase in FL.